2018
DOI: 10.1039/c7ra12377a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of water-degradable silica nanoparticles from carbamate-containing bridged silsesquioxane precursor

Abstract: Silica nanoparticles (SNPs) are attractive for applications for the delivery of drugs and as imaging agents due to their ease of synthesis and scale up, robust structure, and controllable size and composition. Degradability is one important factor that limits biomedical applications of SNPs. With this in mind, we designed, prepared and characterized novel hydrolysable organosilica nanoparticles (ICPTES-Sorbitol SNPs). These particles were prepared by co-condensation of tetraethoxysilane with a bridged sorbitol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Gao et al first reported hollow MONs with pH-triggered degradation based on the hybridization of sorbitol moiety into the silica framework. 45 A sorbitol-bridged alkoxysilane was synthesized by grafting of deliquescent sorbitol to 3-isocyanatopropyltriethoxysilane (ICPTES), and the pH-sensitive hollow MONs were obtained by the hydrolysis and condensation of the mixture containing ICPTES-sorbitol bridged alkoxysilane and TEOS. The results showed that hollow MONs containing sorbitol moiety could occur the hydrolysis at neutral pH and degrade after 3 months, but they were observed to be broken into irregularly spherical pieces only after 3 weeks at pH 4.…”
Section: Mons With Ph-triggered Degradationmentioning
confidence: 99%
“…Gao et al first reported hollow MONs with pH-triggered degradation based on the hybridization of sorbitol moiety into the silica framework. 45 A sorbitol-bridged alkoxysilane was synthesized by grafting of deliquescent sorbitol to 3-isocyanatopropyltriethoxysilane (ICPTES), and the pH-sensitive hollow MONs were obtained by the hydrolysis and condensation of the mixture containing ICPTES-sorbitol bridged alkoxysilane and TEOS. The results showed that hollow MONs containing sorbitol moiety could occur the hydrolysis at neutral pH and degrade after 3 months, but they were observed to be broken into irregularly spherical pieces only after 3 weeks at pH 4.…”
Section: Mons With Ph-triggered Degradationmentioning
confidence: 99%
“…Silica is an excellent material for nanoparticle synthesis because of biocompatibility, post-grafting functionalization, inertness under many conditions, easily to form structured particles and biodegradability. The dissolution of silica consists of three parts: (1) water is adsorbed into the siloxane mesh, (2) siloxane is gradually hydrolysed into silanols and (3) an ion-exchange process, which uses nucleophilic attacks of hydroxyl groups, leads eventually to the leaching of silicic acid (23). The end products diffuse through the bloodstream of the lymph lobe to be eventually cleared in urine.…”
Section: Biodegradabilitymentioning
confidence: 99%
“…For the delivery of anticancer drugs, the degradation of silica nanocarriers in an aqueous environment might be attractive. In that direction, non-porous water-degradable silica nanoparticles were prepared using a bridged sorbitol-based silsesquioxane precursor containing carbamate linkages [ 39 ]. Here, the organosilane-bridge containing precursor was prepared from sorbitol moieties reacted with (3-isocyanatepropyl)triethoxysilane (ICPTES).…”
Section: Degradable Non-porous Organosilica Nanoparticles For Drugmentioning
confidence: 99%